Surveillance system for sustainable tourism with safety and privacy protection - Vacharee Prashyanusorn; Somkuan Kaviya; Preecha P. Yupapin (My University, 2010)
Abstract Nowadays traveling has become the significant and profitable industry which creates huge revenue to all countries around the world. Each country has its own characteristics and outstanding features to attract visitors. One of the most important factors that keep the visitors visiting the destination is the security of the place. Security is one of the keys to sustainable tourism as well. To achieve this, “Security Camera” is a very important tool and plays a highly significant role regarding this matter. Also “Privacy protection” is no very important. “Mobile security camera”, a concept derived from real time surveillance network, aims to prevent and cease crime immediately in active surveillance method as will be discussed later on. The system with safety, privacy protection and cost efficiency for sustainable tourism is also discussed. Finally, to introduce the enough number of cameras with the limited budget, cost efficiency is important.
Keywords: Privacy Protection; Trade Secret Protection Methods